The comparison of interrupted and continuous suturing technique in Snodgrass urethroplasty in patients with primary hypospadias: A systematic review and meta-analysis - Nitinkumar Borkar; Charu Tiwari; Debajyoti Mohanty; Sunita Singh; Anjan Dhua (Urology Annals, 2023)
Background: Hypospadias is among the common congenital anomalies in boys. Snodgrass urethroplasty is one of the most popular techniques for correcting distal and mid hypospadias. Although there is consensus among pediatric surgeons on using absorbable sutures for urethroplasty, there are no established guidelines about the suturing techniques (interrupted suturing [IS] or continuous suturing [CS]) for neourethra creation in Snodgrass urethroplasty. This analysis aims to compare the reported outcomes of both the urethroplasty suturing techniques. Materials and Methods: This systematic review and meta-analysis was conducted as per the preferred reporting items for systematic review and meta-analyses guidelines. A systematic, detailed search was carried out by the authors in the electronic databases – MEDLINE, PubMed Central, Scopus, Google Scholar, and Clinical Trial Registry. Studies were selected and compared based on primary outcomes – development of urethrocutaneous fistula (UCF), meatal stenosis, and secondary outcomes – wound infection, urethral stricture, and operative time. Statistical analysis was performed using a fixed-effect model, pooled risk ratio, and I2 heterogeneity. Results: Five randomized studies with a total of 521 patients met our inclusion criteria. Pooled analysis for total complications, UCF, meatal stenosis, and wound infection showed no significant difference between the CS and IS groups. Subgroup analysis of patients with the use of polyglactin sutures showed a decrease in total complications and UCF in the IS group. Conclusion: There is no difference in total complication rates among the CS and the IS group with the use of absorbable sutures in Snodgrass urethroplasty; however, there is a decrease in the incidence of total complications and UCF in the IS group when polyglactin was preferred over polydioxanone suture for urethroplasty.